162k views
1 vote
I need to simplify for the question

I need to simplify for the question-example-1
User Fastkowy
by
5.1k points

2 Answers

2 votes

Answer:


\tt x^2+3xy+4y^2

Explanation:


\tt(x-2y)^2+7xy\\\\=x^2-4xy+4y^2+7xy\\\\=x^2+3xy+4y^2

User Mackie Messer
by
5.1k points
2 votes

Answer:


x^2 + 3xy + 4y^2

Explanation:


(x - 2y)^2 + 7xy =


= (x - 2y)(x - 2y) + 7xy


= x^2 -2xy - 2xy + 4y^2 + 7xy


= x^2 + 3xy + 4y^2

User BoeroBoy
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.